Prophylactic effects of sauna on delayed-onset muscle soreness of the wrist extensors - Peanchai Khamwong (2018)
© 2015, Sports Medicine Research Center. Background: High-intensity of exercise or unaccustomed eccentric exercise can cause the phenomenon of Exercise-Induced Muscle Damage (EIMD) which usually results in cramps, muscle strain, impaired muscle function and delayed-onset muscle soreness. Objectives: This study investigated the prophylactic efects of sauna towards the symptoms associated with muscle damage from eccentric exercises of wrist extensor muscle group. Patients and Methods: A total of twenty-eight subjects (mean age 20.9 years old, SD = 1.6) were randomly divided into the sauna group (n = 14) and the control group (n = 14). In the sauna group, subjects received sauna before eccentric exercise of the wrist extensor. The eccentric exercises were conducted on the non-dominant arm by using an isokinetic dynamometer. Pain Intensity (PI), Pressure Pain Threshold (PPT) and passive range of motion of wrist fexion (PF-ROM) and extension (PE-ROM) were measured as pain variables. Grip Strength (GS) and Wrist Extension Strength (WES) were measured as variables of wrist extensor muscle function. All the measurements were performed at baseline, immediately after and from 1st to 8th days after the exercise-induced muscle damage. Results: The sauna group signifcantly demonstrated a lower defcit in ROM (passive fexion and passive extension), GS and WES following exercise than that of the control group (P < 0.05). Conclusions: Sauna application prior to the exercise-induced muscle damage demonstrated efectiveness in reduction of sensory impairment (PF-ROM and PE-ROM) and improvement of muscle functions (GS, and WES) in wrist extensor muscle group.